PENGARUH INTERVENSI PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI - Waode Sitti Asfiah Udu; Putu Yayuk Widyani Wiradirani (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Current teenager are very susceptible about risk of healthy damage such as STDS, HIV/AIDS, undesirable pregnancy and abortions. It caused by many factor, one of them is knowledge and attitude of teenagers about reproduction health. The aim of this study is to detect influence of elucidation toward knowledge and attitude of High School students. The method of this study is used pre-experiment design one group pretest-postest. The population is grade XI of high school student and 71 student as a sample. The Data is required by questionnaire and analized by paired t-test. Result of this study show that the rate of score of knowledge and attitude increase after elucidation (p<0,05). The conclusion of this study is elucidation have significantly statistic incease the knowledge and attitude of teenagers about reproduction health.Key words: elucidation, knowledge, attitude, reproduction health